RETRACTED: Syah et al. A New Hybrid Algorithm for Multi-Objective Reactive Power Planning via FACTS Devices and Renewable Wind Resources. Sensors 2021, 21, 5246 - Syah, Rahmad; Khorshidian Mianaei, Peyman; Elveny, Marischa; Ahmadian, Naeim; Ramdan, Dadan; Habibifar, Reza; Davarpanah, Afshin (Sensors (Basel, Switzerland), 2024)
The Sensors Editorial Office retracts the article, “A New Hybrid Algorithm for Multi-Objective Reactive Power Planning via FACTS Devices and Renewable Wind Resources” [...]